The impact of the COVID-19 pandemic on the pilgrimages of Konya Province inhabitants - Küçükkurma, Katarzyna; Skowronek, Ewa (Turyzm/Tourism, 2023)
The article concerns the characteristics and assessment of the Mecca pilgrimage trends among the inhabitants of Konya Province (Türkiye) in 2017–2021, i.e. before and after the outbreak of the COVID-19 pandemic. Particular attention is paid to the impact of the pandemic on: (a) the tourism of the provincial inhabitants to Mecca, (b) the activities of local religious tourism operators, and (c) the sense of psychological discomfort in those who could not participate in a pilgrimage. The study concerned the inhabitants of Konya Province due to the deeply rooted conservatism and high religiosity distinguishing this society. The study was conducted through the methods of investigating sources, expert interview and diagnostic survey. The interviews were conducted at selected Konya travel agencies that organise pilgrimages and at the Konya Valiligi Mudurlugu il Muftulugu. In addition, using an online survey questionnaire, inhabitants of the province were asked if and how their level of psychological comfort was affected by not being able to make the pilgrimage to Mecca during the pandemic. The results showed that the pandemic significantly weakened the previously growing trend of pilgrimages to Islamic holy sites in the analysed community. It also elicited changes in the offers of local tour operators who were forced to open other destinations. To a lesser extent, it affected the feeling of discomfort of provincial inhabitants resulting from the lack of opportunity to make such trips.